2017
DOI: 10.1080/02656736.2017.1324179
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of percutaneous radiofrequency ablation in recurrent hepatocellular carcinoma after liver transplantation

Abstract: Ultrasound-guided percutaneous RFA of recurrent HCC after LT had a high technical success rate and local control. However, RFA cannot decrease the frequency of new tumours or extrahepatic metastasis. The AFP level and tumour number before RFA should be considered to predict the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…The 1-, 3-and 5year OS rates were 68.5%, 40.3%, and 40.3%, respectively. The results were comparable with previous studies, of which 3-year OS rate at 24%-51% was reported [16,17,26]. Moreover, the results of this study revealed that a limited EM before RFA was an independent prognostic factors of OS after RFA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The 1-, 3-and 5year OS rates were 68.5%, 40.3%, and 40.3%, respectively. The results were comparable with previous studies, of which 3-year OS rate at 24%-51% was reported [16,17,26]. Moreover, the results of this study revealed that a limited EM before RFA was an independent prognostic factors of OS after RFA.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the results of this study revealed that a limited EM before RFA was an independent prognostic factors of OS after RFA. When the analysis was limited to patients without limited EM, the 5-year OS rate was 62.4%, which was superior to the aforementioned studies [16,17,26]. Perhaps, as palliative therapy, there is a limited benefit of RFA for intrahepatic tumors, even the metastases are under control.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Enfin la RF est utilisée par certaines équipe comme traitement des récidives intrahépatiques de CHC après transplantation hépatique(67). Cette attitude, si elle n'est pas accompagnée de traitements généraux, est discutable dans le contexte de maladie disséminée.…”
unclassified